Pembelajaran Berdiferensiasi sebagai Inovasi dalam Pengajaran Fiqih di Pondok Pesantren Nurul Iman - Adang Ridwan; Mahdayeni Mahdayeni; Ria Karmila (JOURNAL SAINS STUDENT RESEARCH, 2025)
This study aims to describe the implementation of differentiated learning in the seventh-grade Islamic Jurisprudence (Fiqh) subject at the Nurul Iman Islamic Boarding School (Pesantren Nurul Iman), while also identifying supporting factors, obstacles, and solutions. The research method used a descriptive qualitative approach, with data collection techniques through interviews, observation, and documentation. The research subjects included the Fiqh teacher, homeroom teacher, and seventh-grade students. The results showed that the teachers had implemented the five stages of differentiated learning quite well, starting from mapping learning needs to follow-up. The application of differentiation in content, process, and product has been proven to increase student motivation and engagement in learning. Supporting factors for implementation include teacher commitment, collaboration with homeroom teachers, positive student responses, and conducive classroom conditions. Obstacles that emerged included limited facilities, a lack of understanding of differentiation among some teachers, uneven student readiness, and limited learning time.